2020
DOI: 10.1017/aae.2019.42
|View full text |Cite
|
Sign up to set email alerts
|

Best pasture management practice adoption and sediment abatement

Abstract: Research on producer willingness to adopt individual best pasture management practices (BMPs) is extensive, but less attention has been paid to producers simultaneously adopting multiple, complementary BMPs. Applications linking primary survey data on BMP adoption to water quality biophysical models are also limited. A choice-experiment survey of livestock producers is analyzed to determine willingness to adopt pasture BMPs. Sediment abatement curves are derived by linking estimates of producer responsiveness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Gillespie et al ( 2008) reported higher stocking rates with rotational grazing would decrease net returns relative to higher stocking rates with continuous grazing. Following the findings form Lambert et al (2020), we anticipate the stocking rate parameter estimate to be negative. An increase in the total acres operated is expected to positively influence the likelihood of producers using rotational grazing (Kim, Gillespie, and Paudel, 2008;Lambert et al, 2020).…”
Section: Explanatory Variablesmentioning
confidence: 85%
See 3 more Smart Citations
“…Gillespie et al ( 2008) reported higher stocking rates with rotational grazing would decrease net returns relative to higher stocking rates with continuous grazing. Following the findings form Lambert et al (2020), we anticipate the stocking rate parameter estimate to be negative. An increase in the total acres operated is expected to positively influence the likelihood of producers using rotational grazing (Kim, Gillespie, and Paudel, 2008;Lambert et al, 2020).…”
Section: Explanatory Variablesmentioning
confidence: 85%
“…Adoption Equation Lambert et al (2020) found that willingness to adopt rotational grazing was inversely correlated with stocking density. Gillespie et al ( 2008) reported higher stocking rates with rotational grazing would decrease net returns relative to higher stocking rates with continuous grazing.…”
Section: Explanatory Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…Research on BMP adoption from the producer's perspective is extensive (Adusumilli et al, 2020;Baumgart-Getz, Prokopy, and Floress, 2012;Boyer, Tong, and Sanders, 2018;Claytor et al, 2018;Gillespie, Kim, and Paudel, 2007;Ren et al, 2021;Jensen et al, 2015;Kim, Ferrin, and Rao, 2008;Lambert et al, 2020;Liu, Bruins, and Heberling, 2018;Mishra et al, 2018;Prokopy et al, 2019Prokopy et al, , 2008Roberts et al, 2004, Tong, Boyer, andSanders, 2017). Less frequent are survey studies on the nonagricultural public's willingness to pay (WTP) for programs that provide financial support to farmers for adopting BMPs.…”
Section: Introductionmentioning
confidence: 99%